Threats to the Indonesian Capital Market on the Bankruptcy of PT Asuransi Jiwasyara - Rina Aldila; Yohana Ariska Putri Nasution; Maryam Batubara (Penerbit Jurnal Indonesia, 2022)
Based on the calculation results of the three models above, it can be concluded that the company's performance is generally in good health or has no potential for bankruptcy, this is indicated by the results of testing with the Springate and Grove models. Based on Zmijewski's calculations, the company is categorized as bankrupt. In Table 3 the percentage of predictions and reality in the Springgate and Grover model shows 100% results, this means that the Springate and Grover models are more accurate in predicting the bankruptcy condition of a company. The Zmijewski model has an accuracy rate of 0%. Prediction results with reality are not in line. In the final results of the research based on the Springate and Grover models, the company is said to be in good health or not bankrupt, while the results using the Zmijewski Model are said to be bankrupt, although the research results say the company is bankrupt, in reality the company is still running today.